Implementation of Total Quality Management and Leadership on Islamic Banking Financial Performance - Edy Jumady (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2020)
The goal of this study is to examine the influence of overall quality management and leadership on the financial performance of Islamic banks in Makassar Region. The analysis is quantitative. The population of this research is a permanent staff member of Islamic banks, with as many as 298 workers. The sampling method used simple random sampling and a sample of 75 respondents was collected. Collection of data using a questionnaire. The data analysis methodology used multiple linear regression analyses. Study findings at a 5% level of relevance show that overall quality management and governance have a positive and important impact on financial performance. These findings clarify that the implementation of holistic quality control must concentrate on consumers, performance development, education and training, and employee engagement and empowerment. It is important to include front-line workers in decision-making at their workplaces, as they are the key actors in the development of successful results. Leaders or administrators have been in a position to defend subordinates. They have been shown to be able to increase productivity efficiency in such a way that all the work and goals given have been accomplished in compliance with the wishes of the organization.